Color index : over 1100 color combinations, CMYK and RGB formulas, for print and web media. - Krause, Jim, ....- (Cincinnati (Ohio) : How Design, 2002)
The colour index provides a fantastic wealth of colour and ideas, this clearly and well printed book is great for experienced designers and beginners alike, it clearly provides colours in a pattern form, side by side to give you a clear feel for their association. It will give you great ideas for your colour schemes for any type of design or print work, it covers from soft pastels to vibrant striking colour schemes and many more to fire your creative imagination. The clear RGB and CMYK colour codes make it really easy to put your colour scheme to work immediately within whatever your chosen work application.
Keywords: Kleur